Growth Of Sorghum Plants (Sorghum Bicolor L. Moensh) With Various Varieties And Types Of Biosaka - Talawo, Erik; Mukhtar, Muhammad; Bahri, Syamsul (Jambura Journal of Tropical Livestock Science, 2025)
Abdul Wahid Talawo. NIM. 621421032. The Growth of Sorghum (Shorgum Bicolor (L.) Moench) With Various Varieties and Types of Biosaka. Supervised by Mohammad Mukhtar as the first supervisor and Syamsul Bahri as the second supervisor.This study aims to determine the effect of sorghum varieties and types of biosaka on the growth of sorghum plants. The research was conducted in Tamboo Village, Tilongkabila District, Bone Bolango Regency, Gorontalo Province, from June to September 2024. The study used a two-factor factorial Randomized Complete Block Design (RCBD) where the first factor was sorghum varieties (V) consisting of 2 levels: V1 = Numbu variety, V2 = Kawali variety, and the second factor was biosaka (B) consisting of 3 levels: B1 = Moringa leaves, B2 = Gamal leaves, and B3 = Indigofera leaves, resulting in 6 treatment combinations. Each combination was repeated 3 times, yielding 18 experimental units. The results showed that the application of biosaka significantly affected plant height, number of leaves, and stem diameter. The Numbu variety gave better values compared to the Kawali variety. There was an interaction between the application of biosaka and sorghum varieties on plant height, number of leaves, and stem diameter. The Numbu variety yielded excellent results compared to the Kawali variety in terms of plant height observation, with the Numbu variety reaching 249.21 cm while the Kawali variety only reached 168.57 cm. For the number of leaves, the Numbu variety had 10.45 leaves, while the Kawali variety had only 9.87 leaves. Similarly, for stem diameter, the Numbu variety also showed excellent results with a value of 1.68 cm, while the Kawali variety was only 1.66 cm.Keywords: growth and yield, variety, sorghum, biosaka